Assignment 11

#$&*

course MTH 158

011. `* 11

* 1.2.13 \ 5. Explain, step by step, how you solved the equation z^2 - z - 6 = 0 using factoring.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I reduced z^2 - z - 6 into (z + 3)(z - 2) = 0. Then I did z + 3 = 0 and z - 2 = 0 and got z = -3,2 or (-3,2)

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * STUDENT SOLUTION WITH INSTRUCTOR COMMENT:

I factored this and came up with

(z + 2)(z - 3) = 0

Which broke down to

z + 2 = 0 and z - 3 = 0

This gave me the set {-2, 3}

-2 however, doesn't check out, but only 3 does, so the solution is:

z = 3

INSTRUCTOR COMMENT: It's good that you're checking out the solutions, because sometimes we get extraneous roots. But note that -2 also checks: (-2)^2 - (-2) - 6 = 4 + 2 - 6 = 0. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * 1.2.14 (was 1.3.6). Explain how you solved the equation v^2+7v+6=0 by factoring.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I reduced v^2+7v+6=0 into (v + 6)(v+1) = 0, which I broke down into v + 6 = 0 and v + 1 = 0. After simplifying, I got v =-6, -1 or (-6,-1).

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * STUDENT SOLUTION:

v^2+7v+6=0. This factors into

(v + 1) (v + 6) = 0, which has solutions

v + 1 = 0 and v + 6 = 0, giving us

v = {-1, -6}

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * 1.2.20 (was 1.3.12). Explain how you solved the equation x(x+4)=12 by factoring.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I distributed x and got x^2 + 4x = 12. Then I subtracted 12 and got x^2 + 4x - 12 = 0. Then I simplified this down to (x + 6) (x - 2) = 0. Next I broke the problem in half and did x + 6 = 0 and x - 2 = 0. Finally I got x = -6 and 2.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Starting with

x(x+4)=12 apply the Distributive Law to the left-hand side:

x^2 + 4x = 12 add -12 to both sides:

x^2 + 4x -12 = 0 factor:

(x - 2)(x + 6) = 0 apply the zero property:

(x - 2) = 0 or (x + 6) = 0 so that

x = {2 , -6} **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * 1.2.26 \ 38 (was 1.3.18). Explain how you solved the equation x + 12/x = 7 by factoring.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I multiplied both sides by x and got x^2 + 12 = 7x, then subtracted 7 from both sides and got x^2 - 7x + 12 = 0. Here I simplified the equation to (x - 4) (x - 3) = 0. Then I broke down the equation into x - 4 = 0 and x - 3 = 0 giving me 4 and 3 as answers for x.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Starting with

x + 12/x = 7 multiply both sides by the denominator x:

x^2 + 12 = 7 x add -7x to both sides:

x^2 -7x + 12 = 0 factor:

(x - 3)(x - 4) = 0 apply the zero property

x-3 = 0 or x-4 = 0 so that

x = {3 , 4} **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * 1.2.32 (was 1.3.24). Explain how you solved the equation (x+2)^2 = 1 by the square root method.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I took the square root of each side and got x + 2 = 1 or x + 2 = -1. Working these two separate equations I got -1, -3 as answers for x.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * (x + 2)^2 = 1 so that

x + 2 = ± sqrt(1) giving us

x + 2 = 1 or x + 2 = -1 so that

x = {-1, -3} **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * 1.2.44 (was 1.3.36). Explain how you solved the equation x^2 + 2/3 x - 1/3 = 0 by completing the square.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I couldn’t figure out how to do the completing the squares method. I saw it in the book looked over it but I just couldn’t get it to work for this problem.

confidence rating #$&*: 1

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * x^2 + 2/3x - 1/3 = 0. Multiply both sides by the common denominator 3 to get

3 x^2 + 2 x - 1 = 0. Factor to get

(3x - 1) ( x + 1) = 0. Apply the zero property to get

3x - 1 = 0 or x + 1 = 0 so that

x = 1/3 or x = -1.

STUDENT QUESTION:

The only thing that confuses me is the 1/3. Is that because of the 3x?

INSTRUCTOR RESPONSE:

You got the equation

(3x - 1) ( x + 1) = 0.

The product of two numbers can be zero only if one of the numbers is zero.

So (3x - 1) ( x + 1) = 0 means that

3x - 1 = 0 or x + 1 = 0. You left out this step in your solution.

x + 1 = 0 is an equation with solution x = -1

Thus the solution to our original equation is

x = 1/3 or x = -1.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I feel silly after seeing the solution because that’s exactly how I was going to work the problem but when it told me to complete the squares it threw me off.

------------------------------------------------

Self-critique Rating: 2

*********************************************

Question: * 1.2.50 \ 52 (was 1.3.42). Explain how you solved the equation x^2 + 6x + 1 = 0 using the quadratic formula.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I simply plugged the numbers that were given into the quadratic formula and I got x = -6 ± sqrt 6^2 - 4(1)(1) / 2(1) then after working the problem step by step I got -6 ± sqrt 32 / 2 then I simplified this to -6 ± 4sqrt2 / 2 and finally I divided by 2 and got -3 ± 2sqrt2, or if expanded 3 + 2sqrt2 and 3 - 2sqrt2.

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Starting with

x^2 + 6x + 1 = 0

we identify our equation as a quadratic equation, having the form a x^2 + b x + c = 0 with a = 1, b = 6 and c = 1.

We plug values into quadratic formula to get

x = [-6 ± sqrt(6^2 - 4 * 1 * 1) ] / 2 *1

x = [ -6 ± sqrt(36 - 4) / 2

x = { -6 ± sqrt (32) ] / 2

36 - 4 = 32, so x has 2 real solutions,

x = [-6 + sqrt(32) ] / 2 and

x = [-6 - sqrt(32) ] / 2

Our solution set is therefore

{ [-6 + sqrt(32) ] / 2 , [-6 - sqrt(32) ] / 2 }

Now sqrt(32) simplifies to sqrt(16) * sqrt(2) = 4 sqrt(2) so this solution set can be written

{ [-6 + 4 sqrt(2) ] / 2 , [-6 - 4 sqrt(2) ] / 2 },

and this can be simplified by dividing numerators by 2:

{ -3 + 2 sqrt(2), -3 - 2 sqrt(2) }. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): ok

------------------------------------------------

Self-critique Rating: ok

*********************************************

Question: * 1.2.78 \ 72 (was 1.3.66). Explain how you solved the equation pi x^2 + 15 sqrt(2) x + 20 = 0 using the quadratic formula and your calculator.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

First I plugged the values into the quadratic formula and got x = 15sqrt2 ± [sqrt(15sqrt2) - 4(pi)(20)] / 2(pi). As I worked a little at a time I got 15sqrt2 ± [sqrt(15sqrt2) - 80pi / 2 pi]. After I got here everything began to be very clogged up and confusing.

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Applying the quadratic formula with a = pi, b = 15 sqrt(2) and c = 20 we get

x = [ (-15sqrt(2)) ± sqrt ( (-15sqrt(2))^2 -4(pi)(20) ) ] / ( 2 pi ).

The discriminant (-15sqrt(2))^2 - 4(pi)(20) = 225 * 2 - 80 pi = 450 - 80 pi = 198.68 approx., so there are 2 unequal real solutions.

Our expression is therefore

x = [ (-15sqrt(2)) ± sqrt(198.68)] / ( 2 pi ).

Evaluating with a calculator we get

x = { -5.62, -1.13 }.

DER**

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

Looks like I should have just typed the numbers like 15sqrt2 in on my calculator and just kept going with the numerical values it gave me.

------------------------------------------------

Self-critique Rating: 2

*********************************************

Question: * 1.2.106 \ 98 (was 1.3.90). Explain how you set up and solved an equation for the problem. Include your equation and the reasoning you used to develop the equation. Problem (note that this statement is for instructor reference; the full statement was in your text) box vol 4 ft^3 by cutting 1 ft sq from corners of rectangle the L/W = 2/1.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I couldn’t get this one into word forms. Like on assignment 10 I have trouble setting up equations from word problems, it’s probably my weakest area, once the problems begin to add a number of concepts or when they begin to be more complex in nature.

confidence rating #$&*: 0

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * Using x for the length of the shorter side of the rectangle the 2/1 ratio tells us that the length is 2x.

If we cut a 1 ft square from each corner and fold the 'tabs' up to make a rectangular box we see that the 'tabs' are each 2 ft shorter than the sides of the sheet. So the sides of the box will have lengths x - 2 and 2x - 2, with measurements in feet. The box so formed will have height 1 so its volume will be

volume = ht * width * length = 1(x - 2) ( 2x - 2).

If the volume is to be 4 we get the equation

1(x - 2) ( 2x - 2) = 4.

Applying the distributive law to the left-hand side we get

2x^2 - 6x + 4 = 4

Divided both sides by 2 we get

x^2 - 3x +2 = 2.

We solve by factoring. x^2 - 3x + 2 = (x - 2) ( x - 1) so we have

(x - 2) (x - 1) = 2. Subtract 2 from both sides to get

x^2 - 3 x = 0 the factor to get

x(x-3) = 0. We conclude that

x = 0 or x = 3.

We check these results to see if they both make sense and find that x = 0 does not form a box, but x = 3 does.

So our solution to the equation is x = 3.

x stands for the shorter side of the rectangle, which is therefore 3. The longer side is double the shorter, or 6.

Thus to make the box:

We take our 3 x 6 rectangle, cut out 1 ft corners and fold it up, giving us a box with dimensions 1 ft x 1 ft x 4 ft.

This box has volume 4 cubic feet, confirming our solution to the problem.

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

It’s a bit blurry but after reading through the solution it is beginning to make sense.

------------------------------------------------

Self-critique Rating: 2

*********************************************

Question: * 1.2.108 \ 100 (was 1.3.96). Explain how you set up and solved an equation for the problem. Include your equation and the reasoning you used to develop the equation. Problem (note that this statement is for instructor reference; the full statement was in your text) s = -4.9 t^2 + 20 t; when 15 m high, when strike ground, when is ht 100 m.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

I set up the first part by substituting 15 for s and working the problem as we were working the problems by factoring. I factored out one of the t’s and subtracted 20 from one side giving me -5 = 4.9t. I divided both sides by -4.9 and got a final answer of roughly 1.02 seconds. I had no clue how to find either of the next two answers because I couldn’t think of a way to find when the object would reach its highest point or how long it would momentarily float as momentum shifted from upward to downward momentum.

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

* * To find the clock time at which the object is 15 m off the ground we set the height s equal to 15 to get the equation

-4.9t^2 + 20t = 15

Subtracting 15 from both sides we get

-4.9t^2 +20t - 15 = 0

so that

t = { -20 ± sqrt [20^2 - 4(-4.9)(-15) ] } / 2(-4.9)

Numerically these simplify to t = .99 and t = 3.09.

Interpretation:

The object passes the 15 m height on the way up at t = 99 and again on the way down at t = 3.09.

To find when the object strikes the ground we set s = 0 to get the equation

-4.9t^2 + 20t = 0

which we solve to get

t = [ -20 ± sqrt [20^2 - 4(-4.9)(0)] ] / 2(-4.9)

This simplifies to

t = [ -20 +-sqrt(20^2) ] / (2 * -4.9) = [-20 +- 20 ] / (-9.8).

The solutions simplify to t = 0 and t = 4.1 approx.

Interpretation:

The object is at the ground at t = 0, when it starts up, and at t = 4.1 seconds, when it again strikes the ground.

To find when the altitude is 100 we set s = 100 to get

-4.9t^2 + 20t = 100.

Subtracting 100 from both sides we obtain

-4.9t^2 +20t - 100 = 0

which we solve using the quadratic formula. We get

t = [ -20 ± sqrt (20^2 - 4(-4.9)(-100)) ] / 2(-4.9)

The discriminant is 20^2 - 4 * -4.9 * -100, which turns out to be negative so we do not obtain a solution.

Interpretation:

We conclude that this object will not rise 100 ft. **

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

I didn’t use the quadratic equation which would’ve given me all the pieces I needed to find the answer.

------------------------------------------------

Self-critique Rating: 2

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#Very good responses. Let me know if you have questions. &#